What should I do now? Evaluation of two refresher trainings in the chemical industry to maintain (non)technical skills - Vogel, Olga [Verfasser]; Conein, Stephanie [Verfasser]; Gabriel, Anna-Lena Emmi [Verfasser]; Kluge, Annette [Verfasser] (My University, 2025)
“Introduction: In the context of Industry 4.0, High-Reliability Organizations (HROs) are increasingly shaped by automation and procedural standardization, which limits opportunities for employees to practice critical skills. In non-routine situations such as system failures, this may lead to delayed responses and elevated safety risks. While refresher trainings are well established in aviation and maritime domains, no comparable standard exists in the chemical industry. Methods: Two experimental field studies were conducted to evaluate short-format refresher trainings targeting technical and non-technical competencies. Study 1 (iN = 24) used a virtual reality (VR) simulation to refresh emergency-related technical skills of trainee chemical technicians. Performance, error rates, and knowledge retention were assessed across three measurement points. Study 2 (iN = 45) implemented a gamified, on-the-job non-VR intervention over three sessions to reinforce team resource management (TRM) skills. Pre-post assessments captured the use of TRM competencies and TRM awareness. Results: Both interventions were positively evaluated and demonstrated potential to counteract skill decay under real-world conditions. The VR training resulted in fewer errors, improved performance in emergency scenarios, and faster response times. The TRM intervention showed increases in TRM-related behaviors and awareness. Discussion: The findings indicate that short-format refresher trainings can effectively support the maintenance of technical and non-technical competencies in safety-critical industrial environments. Integrating such targeted refresher formats into operational training strategies may help sustain competence and mitigate risks associated with automation-driven reductions in practice opportunities.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.4.1.4 Verarbeitendes Gewerbe; G 2.2.1 Technologisierung; L 4.2 Mediengestützte Lehr-Lernformen; 370; 600; Chemische Industrie; Chemikant; Digitalisierung; Automatisierung; Qualifikationsanforderung; Trainingsprogramm; Virtuelle Realität; Lernspiel; Handlungskompetenz